SV40 Reporter Viruses - Katzman, Rebecca B. (2008)
Three simian virus 40 (SV40) reporter viruses were constructed in this study. One expresses the green fluorescent protein (GFP) as a fusion protein with the first exon of large-T (LT) antigen and is useful for live-cell imaging. A second reporter virus has a FLAG epitope tag at the C-terminus of large-T (LT) antigen (vC-LT(FLAG)), and a third has the FLAG tag at the N-terminus of LT (vN-LT(FLAG)). The vC-LT(FLAG) construct grows to titers near those of wild-type (WT) virus and functions well as a reporter virus for SV40 infection. The vN-LT(FLAG) construct, while viable, has a defect in the production and spread of infectious particles. All three viruses are useful in detecting superinfecting virus in cells in which nuclear LT is already present, such as persistently infected human mesothelial cells.